Pedestrian Path Choice with Diagonal Streets. Issue 3 (1st September 2016) - Kim, Byungsuk; Kim, Minkyun; Lee, Jiah; Park, Jina
Abstract : The aim of this study is to investigate pedestrian path choice between diagonal and straight streets. We selected 16 streets including both straight and diagonal streets in Seoul for this study. We then investigated the environments and structures of these streets and surveyed pedestrians about which streets they would choose when they had no destination. First, the participants tend to choose diagonal streets. Second, street angle and street width were identified as the structural factors that had the strongest effects on path choice among diagonal streets. Some environmental factors were also found to be significant: presence of sidewalk, road pavement type, commercial use, presence of street trees, and use of the acute angle plot at an intersection. Overall, the results indicated that some structural and environmental factors associated with diagonal streets affected the pedestrian path choice.